2012
DOI: 10.1159/000338654
|View full text |Cite
|
Sign up to set email alerts
|

Expression Pattern of Basal Markers in Human Dental Pulp Stem Cells and Tissue

Abstract: Dental pulp stem cells (DPSC) have been characterized as a multipotent stem cell population, with the ability to differentiate into mesodermal and neural cell lineages. Although ‘de novo’ expression of neural markers after differentiation is mostly considered as proof of differentiation, expression of these markers in undifferentiated DPSC is not well described. Therefore, an immunocytochemical analysis was performed to evaluate the neural marker expression of undifferentiated human DPSC (hDPSC) in in vitro cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 58 publications
7
46
1
Order By: Relevance
“…First reported in 2000 [8], the existence of DPSCs has been confirmed by many laboratories, including ours [13]; however, the exact area of the dental pulp in which they are located is still not well established. A recent study by Martens et al [14] confirmed earlier findings [4,12,15,16] that DPSCs occupy the prevascular niche and, in developing teeth, the cervical niche located near the cementum/dentin zone. A study based on the mRNA expression levels of DPSC markers, including CD166, CD146, and CD105, concluded that in rat molars, ''coronal pulp harbors more SCs than the other regions'' [17].…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…First reported in 2000 [8], the existence of DPSCs has been confirmed by many laboratories, including ours [13]; however, the exact area of the dental pulp in which they are located is still not well established. A recent study by Martens et al [14] confirmed earlier findings [4,12,15,16] that DPSCs occupy the prevascular niche and, in developing teeth, the cervical niche located near the cementum/dentin zone. A study based on the mRNA expression levels of DPSC markers, including CD166, CD146, and CD105, concluded that in rat molars, ''coronal pulp harbors more SCs than the other regions'' [17].…”
Section: Introductionsupporting
confidence: 69%
“…Representative images from these ex vivo studies ( Table S1; Supplementary Data are available online at www.liebertpub .com/scd), indicating that the inactivation of IGF-1R and p38 MAPK selectively stimulates the division of some quiescent DPCs. Interestingly, most of the cells that entered the cell cycle were located near or within CD271-or p75 neurotrophin receptor (p75 NTR )-positive nerve bundles penetrated by blood vessels where the niche for multipotent DPSCs was found [14,15,55].…”
Section: Inactivation Of Igf-1r and P38 Mapk Induces Cycling Of Quiesmentioning
confidence: 99%
“…Of note, the expression of c-MYC, that is not modulated to maintain the stemness-like state in BM-MSC (Roson-Burgo et al, 2014), was unaffected by a low pHe. As DPSC originate from the cranial-derived neural crest cells, we also investigated the expression of the neuronal stem-related markers nestin and p75/NGFR (Mitsiadis et al, 2015;Martens et al, 2012) after exposure to acidic conditions. Similarly to the other mentioned stemrelated markers, these genes were induced by pHe 6.5.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there are non-vascular DPSCs niches. Since cultured DPSCs express neural markers in high percentage (nestin: 92.7 %, NF-H: 42.3 %, GalC: 92.3 %, and βIII-tubulin: 95.9 %) [22], they were used to locate stem cell niches in the pulp of young permanent teeth. Nestin was found to be expressed throughout the tissue and βIII-tubulin was in the subodontoblast zone [23].…”
Section: Cd146mentioning
confidence: 99%